Creating national guidelines for assessing functional and work capacity of recently settled persons. (13th November 2019) - Henriksson, M; Rask, S; Anttila, H; Kuusio, H
Abstract: Problem: The measurement of functioning in clinical practice should be systematic and comprehensive. However, different versions of the same functioning measure are used e.g. by physicians, psychologists, physiotherapists and occupational therapists. The TOIMIA network of experts aims to harmonize and develop the measuring of functioning in Finland. Description of the problem: With increasing immigration to Finland, a specific need for guidelines on how to assess functional and work capacity of recently settled persons was identified. Led by the National Institute for Health and Welfare (mobiTARMO-project, 2017-2020), guidelines for assessing functional and work capacity in the integration phase are in preparation. Results: The guidelines on assessing functional and work capacity in the integration phase include four principles: Functional and work capacity assessment should be done with culturally and linguistically appropriate methods. Assessment should be based on shared expertise of the professional and the client. Assessment should be comprehensive, and take into consideration physical, psychological, social and cognitive functional capacity, activities of daily living, and environmental factors. Assessment should be systematic and lead to further actions and necessary services. The national guidelines will be disseminated as free online access material in the Terveysportti health portal to professionals in clinical practice and research. Lessons: There are specificities to the cross-cultural assessment of functional and work capacity of recently settled persons. National guidelines can be created through broad collaboration of different organizations, as in the TOIMIA network of experts in Finland. Key messages: Jointly agreed principles on how to assess functional and work capacity in the integration phase benefit professionals and clients. National guidelines can be created, disseminated and taken into practice through broad collaboration.